Hepatic granulomata in pyrexia of unknown origin in Sri Lanka - De Mel, W.C.P.; Wijesiriwardena, B.C.; Jayasinghe, K.S.A.; Amarasekera, L.R.; Sheriff, M.H.R.; Dharmadasa, K. (My University, 1983)
Abstract : Eight cases of hepatic granulomata found in the investigation of P. U. O. have been studied. Only 2 of these granulomata showed definite caseation. With the limited investigations available to us and the high incidence of tuberculosis these patients were successfuly treated with anti tuberculous therapy on clinical suspicion. The liver biopsy is a useful diagnostic aid in the management of P. U. O. In the setting of a developing country like Sri Lanka, several aetiological agents may be responsible for hepatic granulomata. Our findings suggest that Anti Tuberculous therapy is valuable in the management of patients with hepatic granulomata in the presence of prolonged fever.